ANALISIS PERBANDINGAN THROUGHPUT PADA SINGLE SERVER DAN CLUSTER SERVER MENGGUNAKAN LOAD BALANCING - Farida, Farida; Azhari, Lukman; Kaaffah, Faiz Muqorrir; Wartono, Wartono (Politeknik Bisnis Indonesia, 2025)
The rapid growth of internet usage has significantly increased the demand for web servers, necessitating efficient resource management solutions. To address this challenge, load balancing has become a crucial strategy for distributing incoming connection requests across multiple servers hosting the same content. This approach enhances performance and service reliability by optimizing workload distribution. This study aims to develop and evaluate a load balancing model using clustered servers to handle high workloads efficiently. The test results indicate that the clustered server system with load balancing consistently achieves higher throughput compared to a single-server-based system. In a single-server configuration, throughput ranges from 2,640 KB/s to 2,677 KB/s, while in a clustered server setting with load balancing, throughput improves to 2,704 KB/s to 2,731 KB/s. These findings underscore the importance of load balancing in ensuring optimal and efficient performance on web servers, both in local and distributed scenarios.